UPAYA PERAWATAN KERUSAKAN INTEGRITAS KULIT PADA PASIEN DIABETES MELITUS DI RSUD dr. SOEHADI PRIJONEGORO - Kustianingsih, Putri Ambar Kustianingsih, Arief W. Jadmiko, S.Kep., Ns., M.Kep (2016)
Background: Results of WHO in 2014, patients of DM up to 422 billion in the world. Prevalance estimated of foot ulcer from approximately 4% to 10% annual, while lifetime risk of diabetic ulcers ranged from 15% to 25%. Wound of diabetic or ulcus diabetic are abnormality in the nerves, blood vessels and infection causes injury. Patients of Diabetes Melitus needs handling from health workers because any problems can arise such as nutritional deficiencies, damage to sskin integrity, limited physical mobility, pain, risk of spread infection, and ulcers. The main actions of nurse can be done independently or nonfarmakologi because this is a role of nurse. Objective: The Writer' s purpose can provided an overview of nursing care for DM patient with damage skin integrity in Tulip room dr. Soehadi Prijonegoro Hospital. Methods: This observation used descriptive method with study case approach in Tulip room dr. Soehadi Prijonegoro Hospital on 28 March 2016 until 30 March 2016. This steps with collected data, analized data, diagnosticated, made plan, took action and nursing cared evaluation. Result: After action for 3x24 hours for DM patients with such as doing medication of the wound care, doing massage around the wound, often change the position of patients, and colaboration with doctor such as give a insulin. Diagnosa of damage to skin integrity is partially resolved and continued intervention such as wound care, gave insulin, repotition, massage, lower extrimity elevation.Actually, this actions have influence in the wound healing process. Conclusion: The problem of nursing damage skin integrity is resolve partially needed continous cared for achieved outcomes. The step that can be used to with other medical teamwork, family andthe patient. The implementation of nuring took effect with wound healing after intervention. This action should be care with damage skin integrity.